2021
DOI: 10.3390/cancers13092273
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Standardized Uptake Values of Oral Squamous Cell Carcinoma in PET-CT on Prognosis, Tumor Characteristics and Mitochondrial DNA Heteroplasmy

Abstract: Under aerobic conditions, some cancers switch to glycolysis to cover their energy requirements. Taking advantage of this process, functional imaging techniques such as PET-CT can be used to detect and assess tumorous tissues. The aim of this study was to investigate standardized uptake values and mitochondrial DNA mutations in oral squamous cell carcinoma. A cohort of 57 patients underwent 18[F]FDG-PET-CT and standardized uptake values were collected. In 15 patients, data on mitochondrial DNA mutations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…These data suggested that leptin promoted glycolysis under hypoxia conditions. Glycolysis is key to BMCSs differentiation and energy uptake, especially in the anoxic environment [ 36 , 37 ]. To determine the changes in glycolysis of BMSCs, the levels of glucose in cells were analyzed by an oxidase method (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that leptin promoted glycolysis under hypoxia conditions. Glycolysis is key to BMCSs differentiation and energy uptake, especially in the anoxic environment [ 36 , 37 ]. To determine the changes in glycolysis of BMSCs, the levels of glucose in cells were analyzed by an oxidase method (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study reviewing 257 patients with OSCC identified that SUV-N ≥ 15.9 and levels IV and V metastasis in the neck were independent risk factors for adverse OS, disease-specific survival, distant-metastasis-free survival (DMFS), and DFS [29]. High values for SUV-T, the denominator of the NTR, were correlated with adverse pathological features of OSCC, such as greater DOI, PNI, tumor grade, and bone infiltration [12,30], and higher SUV-T values predicted occult neck lymph node metastasis in patients diagnosed as having OSCC [31]. However, the prognostic value of SUV-T is inconsistent within the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification of effective tumor-related prognostic biomarkers is of paramount importance to aid in patient stratification and to enable personalized treatment planning. 18 F-fluorodeoxyglucose-positron emission tomography ( 18 F-FDG PET) is extensively employed in pretreatment workup processes for OSCC [12], particularly in those with advanced-stage disease [13]. As described in the literature, in patients with HNC, the maximum standardized uptake value (SUVmax) derived for regional enlarged lymph nodes (SUV-N) and that derived for the primary tumor (SUV-T) exhibit prognostic utility [14,15].…”
Section: Introductionmentioning
confidence: 99%